MiR-338-5p inhibits cell proliferation, colony formation, migration and cisplatin resistance in esophageal squamous cancer cells by targeting FERMT2. (20th December 2018) - Lin, Wen-Chun; Chen, Li-Han; Hsieh, Yao-Chin; Yang, Pei-Wen; Lai, Liang-Chuan; Chuang, Eric Y; Lee, Jang-Ming; Tsai, Mong-Hsun
Abstract: Esophageal cancer is one of the leading causes of cancer death in the male population of Eastern Asia. In addition, esophageal squamous cell carcinoma (ESCC) is the major type of esophageal cancer among the world. Owing to the poor overall 5-year survival rate, novel effective treatment strategies are needed. MicroRNAs are important gene regulators that are dysregulated in many cancer types. In our previous study, we applied next-generation sequencing to demonstrate that miR-338-5p was downregulated in the tumor tissue of patients with versus without recurrence. In this study, we further studied the roles of miR-338-5p in ESCC. The expression of endogenous miR-338-5p was at lower levels in ESCC cells compared with normal cells. Functional assays showed that miR-338-5p reduced cell proliferation, colony formation, migration and cisplatin resistance in an ESCC cell line, CE-81T. Potential target genes of miR-338-5p were identified by microarray and prediction tools, and 31 genes were selected. Among these, Fermitin family homolog 2 ( FERMT2 ) plays an oncogenic role in ESCC, so it was chosen for further study. Luciferase assays showed the direct binding between miR-338-5p and the 3′ untranslated region of FERMT2 . Silencing of FERMT2 inhibited cell proliferation, colony formation, migration and cisplatin resistance. Pathway analysis revealed that the integrin-linked protein kinase signaling pathway, in which FERMT2 participates, was significantly affected by a miR-338-5p mimic. Our results suggest that miR-338-5p may play an antioncogenic role in ESCC via repressing FERMT2 . Abstract : The study demonstrated that miR-338-5p reduced the characteristics of cancer recurrence by down-regulating integrin-linked protein kinase pathway through targeting FERMT2 in the esophageal squamous cell carcinoma (ESCC) cells. Thus, miR-338-5p could be a potential target of ESCC therapy.